Study of tolerance ability in phosphate solubilising microorganisms isolated from tea plantations soil of lower Darjeeling hills - Saha, Sumedha (2023)
Isolated consortia from organic and inorganic tea plantation soils of Darjeeling showing halo was considered for tolerance study. Phorate was most and Deltamethrin was the least tolerant pesticide for the isolated PSM consortia. So, Phorate may be considered as most used or most accumulated pesticide. Erythromycin was most and Ofloxacin was the least tolerant antibiotic while Fluconazole was most and Itraconazole was the least tolerant antifungal agent for the isolated PSM consortia. It was noted that there was no or partial inhibition of PSM growth by some pesticide, antibiotic and antifungal agents. In all the three tolerance studies it was observed that there is no relation between collection sites but in all the assays average inhibition zones were more in organic plantations than inorganic plantations.